Humans - Sarsby, Jo; BBC Learning (Australia: BBC Learning, 2005)
This series visits the crucial moments in life's journey to dominate the earth.' Humans' examined the difference between humans and chimps
Photography, Alastair Mc Cormick ; executive producer, Michael Gunton ; series producer, Miles Barton
Keywords: Human; Human-animal relationships